Hubungan Antara Pola Asuh Berwawasan Jender dengan Cinderella Complex - Neneng Anggriany; Yulianti Dwi Astuti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2003)
This study is aimed at finding a relationship between child rearing practice using gender perspective and Cinderella Complex. Cinderella Complex is a common term used to indicate the tendency among women/female to believe that aspirations for independence, as it relates to their specific gender, is inappropriate.  Women who show Cinderella Complex will see themselves as in need for nurturance,  having inherent need for protection and help from other people. The proposed hypothesis was that there is a negative relationship between child rearing practice using gender perspective and Cinderella Complex.  The participants of the study were 250 female college students from one private university in Yogyakarta, with age ranging from 19-25 years. The data gathered were analyzed using Pearson product moment correlation. The result of the study confirmed the hypothesis: There is a significant negative correlation between child rearing practice using gender perspective with Cinderella complex. Practical implications and relevance for future studies are discussed. Key words: Child rearing practice, gender perspectives, Cinderella Complex.